2015
DOI: 10.1177/1748048515620858
|View full text |Cite
|
Sign up to set email alerts
|

The group-sphere model of international news flow: A cross-national comparison of news sites

Abstract: Why are some countries mentioned very frequently in international news while others are not? Seeking to improve previous explanations in the literature, this study employs a large corpus of news sites in 11 countries and 10 languages over a 3-year period. A systematic computer-driven analysis revealed a similar pattern common to international news in all countries. The best explanation for the prominence of a foreign country in the news included variables from three groups (national traits, relatedness, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Including also adjective might therefore decrease the validity of cross-national comparison. Previous studies (Segev, 2010a, 2015, 2016a, 2016b), however, found that focusing on country names in a high volume of news items provides a very accurate estimate for the actual attention a country gives to another in its news outlets.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Including also adjective might therefore decrease the validity of cross-national comparison. Previous studies (Segev, 2010a, 2015, 2016a, 2016b), however, found that focusing on country names in a high volume of news items provides a very accurate estimate for the actual attention a country gives to another in its news outlets.…”
Section: Methodsmentioning
confidence: 96%
“…Google News as a news aggregator is particularly interesting to study, since it combines a great variety of news sources, and employs secretive automatic algorithms when selecting and prioritizing news items. Although its national channels are language based rather than strictly country based, previous studies found that its international focus is significantly similar to that of print and broadcast news sources of the same nation (Segev, 2016b). In fact, the ranking of foreign countries in any national Google News site was strongly correlated with that of other news sites of the same county and only moderately correlated with the country ranking in the news sites of other countries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the percentage of a country's population that is deemed foreign is a key factor to that country's prominence in the news (Segev, 2015). However, news organizations must constantly determine the "relevance" (Harcup & O'Neill, 2001) of news stories to their audience in accordance with perceived cultural proximity, viewed through a social, political and ideological lens (Segev, 2016) and frame a story accordingly. Thus, examining patterns of frames surrounding refugees around the Americas may help to uncover the cultural importance of this issue to those who attend to that message.…”
Section: Media Framingmentioning
confidence: 99%
“…316-317) (Grasland, 2019). Τα αποτελέσματα νεότερων μελετών του Segev (2015Segev ( , 2016 (Himelboim, Chang, & McCreerym, 2010). Την ίδια στιγμή, λόγω της μεγάλης εξάρτησης του διαδικτύου από τα πρακτορεία και τα παραδοσιακά ΜΜΕ, τα συνήθη στερεότυπα και οι κλασικές αξίες της είδησης, όπως εδώ και χρόνια έχουν αποκρυσταλλωθεί στους κόλπους της δυτικής δημοσιογραφίας, εξακολουθούν να επιβιώνουν, καλλιεργώντας μια εικόνα του μη-δυτικού κόσμου, η οποία παραμένει εμποτισμένη με το «σύνδρομο της καταστροφολογίας» (Williams, 2011, σ.162•Holm, 2001 -Barrett, 2007, σ.182).…”
Section: νέα μέσα νέα τάξη (διεθνούς) πληροφόρησης;unclassified